Giving Green Bean Juice Drink to Increase Breast Milk Production - hasanah Pratiwi Harahap; Novy Ramini Harahap; Risfa Safrida. R (Jurnal MID-Z (MIDWIFERI ZIGOT), 2022)
Breast milk supply can be improved one way to consume mung beans extract that contained protein, iron and vitamin B1. The stuay aimed to determine the effectiveness of provision mung beans to increase breast milk supply in Hj. Ainal Clinic Pidie District. The stuay was quasy experiment with one group pretest-posttest. The population was 22 post-partum mothers in Hj. Ainal mardhiah Clinic. The sample were 11 respondents. Data analysis used T-test and then presented in a tabulation of the frequency distribution. The stuay was quasy experiment with one group pretest-posttest. The population was 22 post-partum mothers in Hj. Ainal mardhiah Clinic. The sample were 11 respondents. Data analysis used T-test and then presented in a tabulation of the frequency distribution. The conclusion in this study is that there is an increase in breast milk production from the baby indicator with a sig value of 0.004 and an increase in breast milk products from the mother indicator with a sig value of 0.003. It is hoped that through research on giving green bean juice to postpartum mothers at the Hj clinic. Ainal Mardiah Aceh Garot can add insight and knowledge for postpartum mothers about the effectiveness of giving green bean juice to breast milk production.